Models and Methods of Islamic Education Planing at SDIT Khoiru Ummah - Mujahidin, Endin; Hartono, Rudi; Supraha, Wido; Andriana, Nesia; Sakinah, Kafa (AT-TURATS, 2024)
The success of building a civilization is fundamentally a key to education. Education is one of the most critical factors in human life, as it facilitates the development of interests, talents, and knowledge. A fundamental aspect of education is the importance of developing effective educational planning methods and models. This study analyzes the methods and models of educational planning implemented in an institution, specifically the Khoiru Ummah Integrated Islamic Elementary School, located in Kalong Jalan. This research employs a qualitative approach. The findings indicate that the methods and models of basic education planning can adopt the comprehensive planning model and Planning, Programming, and Budgeting System (PBBS). These models are deemed more suitable for creating an integrated and comprehensive approach that encompasses all aspects of the school environment.Keberhasilan dalam membangun sebuah peradaban secara fundamental adalah kunci dari sebuah pendidikan. Pendidikan merupakan salah satu faktor terpenting bagi kehidupan manusia, karena pendidikan dapat memudahkan manusia dalam mengembangkan minat, bakat serta ilmu pengetahuan. Salah satu hal yang mendasar dalam sebuah pendidikan yaitu pentingnya mengembangkan metode dan model perencanaan pendidikan. Dalam penelitian ini, penulis menganalisis metode dan model perencanaan pendidikan di sebuah lembaga yaitu sekolah dasar Islam terpadu Khoiru Ummah yang beralamat di Kalong Jalan. Penelitian ini menggunakan penelitian kualitatif deskriptif, dari hasil penelitian ditemukan bahwa metode dan model perencanaan pendidikan dasar dapat mengadopsi model perencanaan komprehensif dan PBBS karena lebih sesuai di dalamnya bisa terintegrasi dan bersifat menyeluruh pada semua lingkup sekolah.